Lectures for the XXIst Century - Raymaekers, Bart (Book collections on Project MUSE., 2008)
What preoccupies scientists today? What is the impact of their ideas and discoveries on ourselves and on our society? This question is the starting point of the 'Lectures for the twenty-first century''. Parallel to the established Dutch series, this year for the first time an English edition was organized. This first English edition offers an international audience a glimpse behind the scenes of the laboratories, the work shops or the studies and shows how linguistic justice, the history of Belgium, Fair Play, food supplies, global change, cultural identity, China and the global environmental.